PENGETAHUAN DAN PERSEPSI IBU HAMIL TERHADAP PEMERIKSAAN TRIPLE ELIMINASI (HIV, SIFILIS, HEPATITIS B) DI KOTA DENPASAR - Widyanthini, Desak Nym; Kurniasari, Ni Made Dian; Harjana, Ngakan Putu Anom; Widyanthari, Desak Made (ARCHIVE OF COMMUNITY HEALTH, 2024)
HIV, syphilis and hepatitis B are sexually transmitted infections that can be transmitted from mother to fetus. The Ministry of Health is holding a triple elimination program in accordance with WHO recommendations to prevent transmission. This research is an analytical study with a cross sectional design, using a questionnaire regarding the knowledge and perceptions of pregnant women regarding triple elimination examinations, at Puskesmas II South Denpasar and UPTD Puskesmas II East Denpasar. Analysis was carried out univariate and bivariate. Of the 85 pregnant women interviewed, the majority had good knowledge (97.6%), negative perception (55.3%). Respectively, 29.4%, 32.9% and 1.8% of pregnant women admitted that they had not carried out an HIV test, the majority of pregnant women who were in the second trimester were tested for syphilis and Hepatitis B. The research results also show that the variables number of living children and last education are significantly related to mother's knowledge. It is necessary to strengthen the integrated antenatal care system (10T) and collaborate with independent midwife practices and obstetrician practices for triple elimination examinations as early as possible. Keywords:  HIV, Hepatitis, Pregnant Women, Denpasar City, Syphilis